Five-year Follow-up of Transobturator Sling: 152 Cases with the Same Surgeon - Diniz, Mucio Barata; Diniz, Luisa Campos Barata; Lopes da Silva, Gustavo Francisco; Filho, Agnaldo Lopes da Silva; Reis, Zilma Silveira Nogueira; Monteiro, Marilene Vale de Castro (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To evaluate the long-term subjective cure rate of the transobturator sling, including an analysis of the risk factors and of the impact of increased surgical experience on the results.Methods A retrospective cohort study of women who underwent transobturator sling surgery from 2005 to 2011 was conducted. Patients were evaluated by a telephone survey using the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) and by subjective questions regarding satisfaction. An ICIQ-SF score of 0 was considered a cure. The crude and adjusted odds ratios and 95% confidence intervals were estimated in univariate and multivariate logistic regression models to identify risk factors for surgical failure. Differences with p < 0.05 were considered significant.Results In total, 152 (70.6%) patients answered the questionnaire. The median follow-up period was 87 months. The urodynamic diagnosis was stress urinary incontinence in 144 patients (94.7%), and mixed urinary incontinence in 8 (5.3%) patients. Complications occurred in 25 (16%) patients. The ICQ-SF results indicated that 99 (65.10%) patients could be considered cured (ICIQ-SF score = 0). Regarding the degree of satisfaction, 101 (66%) considered themselves cured, 43 (28%) considered themselves improved, 7 (4.6%) considered themselves unchanged, and one reported worsening of the incontinence. After the univariate and multivariate analyses, the primary risk factor for surgical failure was the presence of urgency (p < 0.001).Conclusion The transobturator sling is effective, with a low rate of complications and a high long-term satisfaction rate. The risk factors for failure were the presence of urgency and patient age. The increased experience of the surgeon was not a factor that influenced the rate of complications.
Keywords: stress urinary incontinence; suburethral support; transobturator sling